(untitled) - Knizka, Jan; Klapita, Vladimir; Lopata, Jan (Doprava a spoje, 2005)
Necessary condition for improving of railway companies' work is to reduce the time needed for judging time and for realization of special loads transportation in international rail freight traffic. In this paper is system concept of ZSR lines coding at type transport of special loads.